THE KEY FINDINGS OF THE COURIER, EXPRESS AND PARCEL SERVICES - Madlenakova, Lucia (Doprava a spoje, 2010)
Today, a customer can choose from a variety of offers and providers of courier express and parcel services. The basic marks of these services is the provision value-added, door-to-door transport and deliveries of next-day or time-definite shipments, including documents, parcels and merchandise goods. Now the European CEP market is characterized by increasing consolidation, moderate growth rates and rising operational costs.